Bubble-crash experience and investment styles of mutual fund managers - Luo, Deming; Yao, Zhongwei; Zhu, Yanjian (Journal of Corporate Finance, 2022)
This study examines the effect of fund managers' bubble-crash experience on their investment styles. Using the 2007–2008 and 2014–2015 bubble-crash events of China's A-share market, we find that managers who experienced a stock market crash are more value-oriented in their portfolios. While the effect of firsthand bubble-crash experience on investment style is significant, we find little evidence of the impact of secondhand experience gained from institutional memory or the management team. We explain these findings using incomplete information learning theory, salience theory, and the change in risk preferences. Moreover, different investment styles across manager types affect fund performance around the time the new bubble burst in June 2015. Managers with 2007–2008 bubble-crash experience and a more value-oriented investment style have lower (higher) fund returns than those without such experience before (after) the bubble burst.